Perkawinan Ulang Pemimpin Gereja:: Analisis Sosio Teologis atas Pendeta Pasca Ditinggal Pasangan - Simon, Simon; Anderson, Lindin (STT Bala Keselamatan Palu, 2025)
Abstract: The focus of this article is the phenomenon of remarriage among church leaders, particularly male and female pastors who have lost their spouses. Although the experience has a significant impact on the personal lives and individual ministries of the pastors, this research is based on the lack of comprehensive studies regarding the socio-theological aspects of that experience. The main research question of this article is, how does the socio-theological context of marriage influence church leadership? This article is written using a qualitative methodology with a multiple-case study. The findings of this article reveal that the remarriage of church leaders often elicits a range of responses from the congregation, from acceptance to rejection. This also affects the social relations and leadership authority of the pastor in the church. Additionally, church leaders face spiritual and emotional pressure when deciding to remarry. Therefore, the church must create more empathetic and inclusive pastoral guidelines to support leaders in the remarriage process while they are in a state of mourning. Furthermore, the church should provide opportunities for theological discussions on this issue. Abstrak: Fokus artikel ini adalah fenomena pernikahan ulang di kalangan pemimpin gereja, khususnya pendeta pria dan wanita yang kehilangan pasangannya. Meskipun pengalaman tersebut memiliki dampak yang signifikan pada kehidupan pribadi dan pelayanan individu kepada para pendeta, penelitian ini didasarkan pada kurangnya studi komprehensif mengenai aspek sosio-teologis dari pengalaman tersebut. Rumusan pertanyaan utama artikel ini adalah, bagaimana konteks sosio-teologis perkawinan dalam kepemimpinan gereja? Artikel ini ditulis menggunakan metodologi kualitatif dengan studi kasus. Temuan artikel ini mengungkapkan bahwa perkawinan ulang pemimpin gereja sering menimbulkan respons yang beragam dari jemaat, mulai dari menerima hingga menolak. Ini juga memengaruhi relasi sosial dan otoritas kepemimpinan pendeta di gereja. Selain itu, pemimpin gereja menghadapi tekanan spiritual dan emosional saat memutuskan untuk menikah kembali. Oleh sebab itu, gereja harus membuat pedoman pastoral yang lebih empatik dan inklusif untuk mendukung para pemimpin dalam proses perkawinan ulang saat mereka dalam keadaan duka. Selain itu, gereja harus memberikan kesempatan untuk adanya diskusi teologis tentang masalah ini